The Pollen Coat Proteome: At the Cutting Edge of Plant Reproduction - Rejón, Juan David (Proteomes, 2016)
The tapetum is a single layer of secretory cells which encloses the anther locule and sustains pollen development and maturation. Upon apoptosis, the remnants of the tapetal cells, consisting mostly of lipids and proteins, fill the pits of the sculpted exine to form the bulk of the pollen coat. This extracellular matrix forms an impermeable barrier that protects the male gametophyte from water loss and UV light. It also aids pollen adhesion and hydration and retains small signaling compounds involved in pollen–stigma communication. In this study, we have updated the list of the pollen coat’s protein components and also discussed their functions in the context of sexual reproduction